Effects of climate change on grain productivity in Nigeria (1970-2014). Issue 1 (February 2020) - Bamiro, O M; Adeyonu, G A; Babatunde, A; Solaja, S O; Sanni, S A; Faronbi, O A; Awe, T E
Abstract: This study examines the effect of climate change on the yield for four main grain crops in Nigeria (sorghum, maize, millet and rice) over the period 1970-2014. Cobb Douglas and Maximum Likelihood Estimation were explored to obtain reliable estimates. Results suggests that climate have diversified effects on grain yield and variability which shows that as the climate becomes warmer, higher yield variability can be observed on these selected crops. In addition more rainfall increases the yield variability on sorghum, maize, millet and rice. The increasing variation on rainfall also increased crop yield variability on rice. Based on the empirical findings it can be concluded that climate change, through an increase in actual average temperature and changing rainfall pattern has resulted to a decline in productivity of most food grain crops. This effect varies within crops and there is need to adapt different policies for various crops to mitigate the adverse effect of climate change in Nigeria.